Efficacy of ceftazidime-avibactam with or without polymyxin for carbapenem-resistant Klebsiella pneumoniae infections after initial treatment with polymyxin - Jingli Lu; Yani Ma; Zhe Cao; Baoling Zhu; Luna Fan; Haiyang Meng (Microbiology Spectrum)
ABSTRACT Although polymyxins are a suboptimal option for difficult-to-treat resistant infections, they are still preferred as the first-line treatment, especially in low- and middle-income countries. This study assesses the efficacy of ceftazidime-avibactam (CAZ-AVI) following polymyxin B failure in patients with carbapenem-resistant Klebsiella pneumoniae (CRKP) infections. We retrospectively reviewed cases of infections caused by CRKP in adults who received CAZ-AVI as salvage therapy. Clinical features and outcomes were described, and a logistic regression model was used to assess the risk factors associated with in-hospital crude mortality. One hundred and six patients were included in this study. The median age was 56 years. The most common infectious sites were lung. The patients received CAZ-AVI as salvage therapy for a median duration of 9 days following initial treatment with polymyxin B (median, 12.5 days). Also, 91 (85.8%) patients received CAZ-AVI combination therapy, and 34 (32.1%) patients received CAZ-AVI in combination with polymyxin B. The rate of in-hospital crude mortality was 25.5% (27/106), with the highest rate observed in patients treated with regimens containing polymyxin B (41.2%; 14/34). Therapeutic response was observed in 81 (76.4%) patients, with microbiological eradication achieved in 77.1% (74/96) of cases. Multivariable analysis identified that the length of intensive care unit stays, the sequential organ failure assessment (SOFA) score at CAZ-AVI withdrawal, and regimens containing polymyxin B were independently associated with in-hospital mortality, whereas the duration of CAZ-AVI treatment was independently associated with survival. CAZ-AVI salvage therapy demonstrated improved survival outcomes in patients who experienced failure with polymyxin B therapy.IMPORTANCEFor patients with carbapenem-resistant Klebsiella pneumoniae (CRKP) infections, published experience with salvage therapy is limited after the failure of polymyxin-based initial therapy. Here, we found that ceftazidime-avibactam salvage therapy for patients with CRKP infections offers benefit in mortality.